DESIGN AND SIMULATION OF COMBUSTOR FOR TURBOCHARGER BASED MICRO GAS TURBINE SYSTEM USING LPG AND BIOGAS - FEBRIANDA (NIM : 13105017); Pembimbing 1: Dr. Ir. T. A. Fauzi Soelaiman; Pembimbing 2 : Dr. Ir, RUSKA
Nowadays, as the demand of electrical energy escalates, many efforts have to be performed to find altenative energy that can fulfill that demand. The turbocharger based gas turbine system is one of solutions that has good prospect to be applied in remote areas due to its low investment cost. But, the application of this system is still limited to using of LPG as the fuel although biogas has huge potency in the remote area. Based on the fact that the main component of micro turbocharger based gas turbine in producing energy is the combustor, the objective of this research is to obtain the best design dan optimal condition of combustor that can be applied by using LPG and biogas. This research was performed in three main steps which are validation of old combustor, modelling of new combustor using of LPG, and modelling of new combustor using biogas. The simulation was done by using Autodesk Inventor software to create the 3D’s models, Gambit to make the mesh models of combustor, and Fluent to simulate the model. The design process of combustor is carried out based on the empiric method of Lefebre’s experiments in 1983, done on a steady simulation condition, and limited to the fluid models that are available in Fluent. The optimal operation condition of the new combustor using biogas was obtained by varying the mass flow of biogas (0,0021; 0,0023; 0,0025; 0,0027;0,0029; 0,0031; and 0,0033kg/s) and the biogas pressure (25, 35, dan 45 psig). From the analysis and simulation performed, it can be concluded that the simulation that has been done have good level of confidence, proved by the difference of simulation and experiment results whis is not bigger than 5%, the old combustor didn’t present good performancy level due it’s pressure loss (the pressure loss of old and new combustor are 14% and 6%) and outlet temperature (the temperature of old and new combustor are 1119K dan 937K), and the new combustor demonstate the optimal performance in biogas and LPG operation.